اتجاهات الاساتذة الجامعين نحو التعليم بمواقع التواصل الاجتماعي فايسبوك نموذجا - (:unkn) unknown (My University, 2020)
ملخص تهدف هذه الدراسة التً تبنت تطبٌق مدخل الاستخدامات و الاشباعات إلى وصف و تحلٌل اتجاهات الأساتذة الجامعٌن نحو استخدام مواقع التواصل الاجتماعً فً التعلٌم من خلال طرحها التساؤل الرئٌسً التالً: كٌف ٌستخدم الأساتذة الجامعٌن مواقع التواصل الاجتماعً _فاٌسبوك_ فً التعلٌم العالً ؟ وقد تفرع عن هذا السؤال ثلاث تساؤلات فرعٌة على النحو التالً : - هل تهتم جامعة عبد الحمٌد بن بادٌس بالتعلٌم بمواقع التواصل الاجتماعً ؟ - ماهً دوافع إقبال الأساتذة الجامعٌن على مواقع التواصل الاجتماعً فً عملٌة التعلٌم ؟ - ما موقف الأساتذة الجامعٌن من التعلٌم باستخدام مواقع التواصل الاجتماعً ؟ وقد أجرٌت هذه الدراسة فً السنة الجامعٌة 2020_2019مستخدمة استمارة الاستبٌان لقٌاس الاتجاه كأداة لجمع البٌانات أٌن تم توزٌعها على عٌنة مكونة من 51أستاذ بالجامعة بمختلف تخصصاتها ونحن نتأسف لقلة إعداد العٌنة لسبب جائحة كورونا فلم نستطع الوصول لكل اٌماٌلات الأساتذة .وقد شملت الاستمارة عدة أسئلة فمنها من ٌتعلق بخصائص العٌنة ومنها بمدى اهتمام الجامعة بتوفٌر الوسائل اللازمة للتعلٌم بمواقع التواصل الاجتماعً و فً الأخٌر عبارات لقٌاس موقف الأساتذة الجامعٌن من مواقع التواصل الاجتماعً التعلٌمٌة. بعد تطبٌق هذه الأداة البحثٌة وتحلٌل البٌانات تم التوصل إلى نتائج أهمها : - للأساتذة الجامعٌن اتجاه محاٌد نحو اهتمام الجامعة بتوفٌر التكنولوجٌات اللازمة للعملٌة التعلٌمٌة باستخدام مواقع التواصل الاجتماعً . - للأساتذة الجامعٌن اتجاه قوي نحو دور مواقع التواصل الاجتماعً فً توفٌر الوقت و الجهد لكلا الطرفٌن. - للأساتذة الجامعٌن اتجاه كبٌر نحو إسهام مواقع التواصل الاجتماعً فً تثبٌت المعلومات و إثراء العملٌة التعلٌمٌة و القضاء على الملل . - تختلف اتجاهات الأساتذة نحو دوافع الإقبال باختلاف التخصص المدرس.RESUME This study which adopted the application of the usage and gratification approach aims to describe and analyze the university teachers attitudes towards the use of social networking sites in education by asking the following main question: how do teachers of university use social networking sites « Facebook » in education ? Under this question we have three sub-questions as follows : _ Does the university of Abd-lhamid Ibn Badis interested in education on social media ? _ What are the causes that push the university teachers in social networking ? _ What is the opinion of university on education using social networking sites ? This study applies the approach of the use and the satisfactions on 2019_2020 .We have choosen a sample composed of 51 teacher with different specialities from university .And we regret the lack of the sample preparation due to the corona virus ,and we could not access to all the emails of the teachers . This questionnaire include several questions ,some of them related to the characteristics of the sample ,including the extent of the university interest in providing the necessary means for education in social media sites ,and also the motives of the teachers interest in using social media sites ,and in the last phrases to mesure the teachers position on educational social media sites . After appliying the reaserch and analizing the data we reached to the important results: _ The university teachers have a neutral tendency towards the university interest in providing the technologies necessary for the educational process using social media . _The university teachers have a strong trend towards the role of social networking sites in saving time and effort for both parties . _The university teachers have a great trend towards using social networking sites to stabilize information ,enrich the educational process and eliminate boredom . _The teachers targets of using differ according to their specialities .
Keywords: الاساتذة الجامعيين،التعليم،مواقع التواصل الاجتماعي